2021
DOI: 10.4102/sajim.v23i1.1313
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance and use of online shopping in Limpopo province

Abstract: Background: The retail industry globally provides online shopping services to offer consumers easy access to a variety of shopping services. Like retailers in other countries, the retail industry in South Africa offers online shopping services to its consumers. South African consumers in Limpopo province are still reliant on the traditional shopping method, despite the convenience, ease of access and the elimination of physical boundaries offered by online shopping.Objectives: This article investigated and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This finding is similar to that of Gharaibeh et al (2018) who suggest that customers are more likely to use banking applications if they find the banking transaction easy to complete. Moeti et al (2021) also believe that undue complexity of an online shopping process negatively affects consumer intention to use online shopping.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to that of Gharaibeh et al (2018) who suggest that customers are more likely to use banking applications if they find the banking transaction easy to complete. Moeti et al (2021) also believe that undue complexity of an online shopping process negatively affects consumer intention to use online shopping.…”
Section: Discussionmentioning
confidence: 99%
“…Physical stores are still threatened by South Africa's growing popularity of online shopping (Bu et al, 2020). Online shopping is said to have several advantages over traditional brick-and-mortar stores, including reduced costs, convenience, cost savings and personalised service (Moeti et al, 2021). To remain competitive for brick-and-mortar stores, recommendations still centre on enhancing the buying experience in actual stores (Angula and Zulu, 2021;Kotler and Armstrong, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Physical stores are still threatened by South Africa's growing popularity of online shopping (Bu et al ., 2020). Online shopping is said to have several advantages over traditional brick-and-mortar stores, including reduced costs, convenience, cost savings and personalised service (Moeti et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Daroch, Nagrath and Gupta (2020) noted that among the factors constraining consumers to shop online included fear of bank transactions, insecurities, services, experiences and trust. Similarly, in Africa, various studies (Moeti, Mokwena & Malebana, 2021;Mofokeng, 2021;Oloveze et al, 2022) have mentioned attributes that restrain consumers from shopping online. In Nigeria, Oloveze et al (2022) found that online shopping by consumers was directly affected by attitude, perceived usefulness and social influences.…”
Section: Introductionmentioning
confidence: 99%